(untitled) (Research, Society and Development, 2026)
Introduction. The choice of mesh type for abdominal wall reconstruction in complex hernia repairs, especially in contaminated surgical fields, has been the subject of increasing debate in surgical practice. Objective. This study aimed to compare the clinical outcomes associated with the use of synthetic, biological, and biosynthetic meshes in complex hernia repairs, with emphasis on hernia recurrence, infectious complications, length of hospital stay, and hospital costs. Methodology. This is a narrative review of the literature, with selection of studies published between 2015 and 2025 in the PubMed, Scopus, Web of Science, Google Scholar, and Cochrane Library databases. Meta-analyses, systematic reviews, and comparative studies presenting quantitative data on the main clinical outcomes were included. Results and Discussion. Analysis of the nine selected studies indicated that synthetic meshes, even in contaminated environments, are associated with lower recurrence rates and significantly lower costs, without a proportional increase in infection rates. In contrast, biological meshes showed inferior outcomes in several studies. Biosynthetic meshes, such as RBOR, demonstrated promising performance, particularly in high-risk patients, although long-term studies are still lacking. Conclusion. Current evidence supports synthetic meshes as the first choice in complex hernia repairs, including contaminated fields. Biosynthetic meshes emerge as a promising intermediate alternative, and material selection should consider the patient’s clinical profile, associated costs, and institutional availability.